Spatio-temporal Evolution of Land Surface Temperature and Its Response to LULC in the Urban Agglomeration of Central Yunnan - LIN Zhiqiang; PENG Shuangyun; SHI Shuangfu; HUANG Bangmei; MA Dongling; ZHU Ziyi; MA Xiaoliang; GONG Luping (Shuitu Baochi Xuebao)
[Objective] To investigate the spatial and temporal variations of land surface temperature (LST) in central Yunnan urban agglomeration and its relationship with land use/land cover (LULC) types. [Methods] Based on Google Earth Engine (GEE) platform, LST was inverted using Landsat satellite image data of central Yunnan urban agglomeration region from 1990 to 2020, and was analyzed using Sen-MK trend analysis, mean-standard deviation method, urban thermal field variance index (UTFVI) and correlation analysis were used to quantitatively analyze the spatial and temporal variations of LST and its response to LULC types in central Yunnan urban agglomeration from 1990 to 2020. [Results] (1) There were significant spatial and temporal differences in interannual temperature classes in central Yunnan urban agglomeration. The mesothermal area always occupied an absolutely dominant position (40%), but its area share decreased year by year. (2) From 1990 to 2020, the areas with UTFVI 0 showed an increasing trend year by year, and the areas with UTFVI > 0.02 showed a decreasing trend, and the ecological and thermal environments were gradually improved. (3) There were response differences in LST for different LULC types. Among them, LST was significantly positively correlated with the proportion of built-up area (r > 0.70). LST was always the lowest in the water area, with a multi-year average temperature of 17.38 ℃, while the highest temperature was found in the area covered by built-up land and cropland, with multi-year average temperatures above 21 ℃. (4) The rapid expansion of cities in the central Yunnan urban agglomeration had resulted in significant changes in LULC. The built-up land area had increased by more than 100.29%, and the rapid development of cities had increased LST from 1990 to 2020. [Conclusion] LULC is an important factor affecting the LST, and reasonable configuration of LULC structure can improve the thermal environment of urban agglomeration. The study's results can provide important insights for rational development planning and improvement of ecological conditions in the urban agglomeration of central Yunnan.